Agreeable News from Persia Iran in the Colonial and Early Republican American Press, 1712-1848 - Potts, D.T. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2022)
Eighteenth and nineteenth century European, British and American newspapers constitute a rich and largely untapped source of contemporary, often eyewitness accounts of historical events and opinions concerning Iran from the late Safavid (1712) through the Qajar (c. 1797-1920) period. This study collects and annotates thousands of articles published in the Colonial and early Republican American newspapers, from the first mention of events in Persia in the American press (1712) to the death of Mohammad Shah (1848), unlocking for the first time a wealth of information on Iran and its place in the world during the 18th and early 19th century. The Editor D.T. Potts is Professor of Ancient Near Eastern Archaeology and History at the Institute for the Study of the Ancient World, New York University.
Preface -- List of American newspapers represented in the collection, with place of publication -- Glossary of archaic or corrupt spellings of personal names, placenames, titles, etc -- 1. The overthrow of Shah Soltan Hoseyn, the demise of the Safavids and Afghan rule -- 2. Peter the Great's Persian Adventure and its Aftermath -- 3. Tahmasp Qoli Khan, later known as Nader Shah -- 4. Civil war and the establishment of Zand rule -- 5. The struggle for power and the triumph of Aqa Mohammad Shah, founder of the Qajar dynasty -- 6. Fath 'Ali Shah, Napoleon and British and East India Company diplomacy -- 7. The First Russo-Persian War and its Aftermath -- 8. The assassination of Griboyedov, the Russian ambassador -- 9. The Second Russo-Persian War and its Aftermath -- 10. The death of 'Abbas Mirza and the installation of Mohammad Shah -- 11. The siege of Herat and its Repercussions -- 12. American missionaries and their French rivals at Urmia -- 13. The Turco-Persian Boundary -- 14. The last years of Mohammad Shah -- 15. Miscellaneous topics (earthquakes, cholera outbreaks, horticultural and other scientific issues) -- Bibliography -- Index.
Keywords: America-History.; Middle East-History.; History of the Americas; History of the Middle East